(untitled) (Research, Society and Development, 2022)
Fungi of the genus Penicillium produce secondary metabolites that are used as a model for the synthesis and development of antibiotics such as Penicillin, Penicillin V, Ampicillin, Amoxicillin and Griseofulvin. The production of such compounds can be explored through small changes in physical and chemical parameters of the crop. These changes stimulate silenced biosynthetic pathways and this increases the diversity of bioactive compounds produced by the fungus. Therefore, the aim of the present study was to investigate the antimicrobial potential of Penicillium spp. isolated in the state of Amazonas. The strains studied in this work are deposited in the Coleção de Fungos da Amazônia (CFAM) of the Instituto Leônidas e Maria Deane (ILMD), and were reactivated in PDA medium for seven days. For the production of extracts, a spore suspension solution was used at a concentration of 1 x 10-6 CFU/mL. 50 µL of this suspension was inoculated into erlenmeyers containing 25 mL of BDL, SB, YES and ISP2 media. The experiment was carried out in triplicate, in static mode, incubated at 28 ºC for 15 days. After this period, the fermented broth was extracted with ethyl acetate and the mycelium with methanol. Then, the Minimum Inhibitory Concentration - MIC of the extracts obtained in ethyl acetate against the pathogens Candida albicans, Candida tropicalis, Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis and Staphylococcus aureus was determined. The best activities were observed for the P. oxalicum and P. citrinum strains cultivated in BDL and SB with MIC of 250 µg/ml and 62.5 µg/ml, respectively.